THE GENUS COELOSTEGIA*) Benth. (Bombac.) - W. SOEGENG REKSODIHARDJO (BRIN Publishing (Penerbit BRIN), 1960)
1. The genus Coelostegia is confined to Western Malaysia: Malay Peninsula, Sumatra and Borneo. 2. Five species (three of which, C. chartacea, C. kostermansii and C. neesiocarpa are new to science) are described. 3. A key to the species is presented.